The relationship between disturbing thoughts (rumination, worry) and sleep quality of pregnant mothers referring to health centers affiliated to Isfahan University of Medical Sciences 2019 - Hadise Enteshari Najaf Abadi; Mahnaz Noroozi; Fatemeh Shaghaghi; Hadise Safinejad; Zahra Mohebbi-Dehnavi (Mashhad University of Medical Sciences, 2022)
Introduction: Hormonal changes during pregnancy affect the sleep-wake cycle and sleep structure and lead to sleep disorders. Ruminants and anxiety are two negative thoughts that can affect the quantity and quality of sleep and cause sleep disorders. Therefore, this study was conducted with aim to determine the relationship between disturbing thoughts (rumination, worry) and sleep quality of pregnant mothers.Methods: This cross-sectional descriptive study was performed in 2019 on 190 pregnant mothers referring to the health centers in Isfahan. Data collection tools were the questionnaires of ruminant, anxiety and sleep quality. Data were analyzed by SPSS software (version 22) and Spearman and regression tests. P<0.05 was considered statistically significant.Results: In pregnant mothers participating in the study, the mean overall score of sleep quality was 2.57±5.60, mental rumination was 9.62±1.43 and anxiety was 33.52±3.37. Based on the results of Spearman test, there is a significant inverse relationship between all dimensions of sleep quality and overall sleep quality score with the overall score of mental rumination and anxiety (p=0.001).Conclusion: There was a significant relationship between rumination disturbing thoughts and anxiety with the quality of sleep in pregnant mothers. For this purpose, by examining the components of disturbing thoughts and their relationship with the quality of sleep in pregnant mothers, an effective step can be taken to improve the quality of sleep of pregnant women.